Commercial relations of Kazakhstan and Russia in the XVI-XVIII centuries (Journal of history, 2020)
This article gives a brief overview of some works, based on the axiology analysis of historical researches process of accumulation of empirical knowledge and becoming of the theoretic-conceptual bases in studying a problem of Kazakh-Russian commercial relations in ХVI-ХVIII centuries. The urgency of a theme of research caused by necessity of development of historiographical aspects of actual problems of history of Kazakhstan, and for objective reconsideration of many pages of Kazakh-Russian relations in ХVI-ХVIII centuries from positions of new methodological approaches in a domestic historical science. As one of modern conceptual installations in studying history of Kazakhstan the withdrawal from consideration of historical processes in a vein of exclusively «Russian» and «Soviet» history and the set ideological imperatives that was characteristic for the Soviet historiography of problems of Kazakh-Russian relations. In conditions of independence of Republic of Kazakhstan on the foreground, only left insufficiently known and not studied aspects of this difficult and inconsistent problem. Key words: historiography, empire, colonization, commercial relations, diplomacy.